PERBEDAAN PREFERENSI KONSUMEN GENERASI Z ANTARA COFFEE SHOP BESAR DAN COFFEE SHOP KECIL DI KECAMATAN COBLONG KOTA BANDUNG - Desty Nadirah Putri; Yosini Deliana (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2020)
Coffee consumption in Indonesia continues to increase in 2014-2018, making entreprereneurs interested in establishing coffee shops with different classifications. The number of businesses engaged in similar fields has led to competition among coffee shop entrepreneurs. One effort in facing competition is by knowing consumer preferences in order to form the right market segmentation. Lifestyle developments and mindset make almost all generations ever drink coffee including generation Z, which is the youngest potential consumer because it has unique characteristics. Kelurahan Lebak Gede is a place of activity for the Z generation because there are many coffee shops and close to schools or universities. The purpose of this study is to identify the characteristics of generation Z coffee consumers based on demographics, psychography, coffee shop attributes, and identify differences between large coffee shop consumers and small coffee shops consumers. The selection of samples in this study used systematic random sampling techniques with a sample of 88 at a large coffee shop and 68 at a small coffee shop. The analysis used is descriptive analysis, and discriminant analysis. The research results show that there are significant differences in the characteristics of age, consumption intensity, time spent in the coffee shop, and visiting time.